2016
DOI: 10.21109/kesmas.v10i4.839
|View full text |Cite
|
Sign up to set email alerts
|

Birth Intervals among Multiparous Women in Indonesia

Abstract: Maternal mortality rate and infant mortality rate in Indonesia are currently high. One of factors causing the high risk of maternal and infant mortality is too short birth intervals. This study aimed to learn determinants of birth intervals among multiparous women in Indonesia. This study used data from the Indonesia Demographic and Health Survey 2012 with 9,945 multiparous women. The data was analyzed using Mann Whitney, Kruskal Wallis and logistic regression tests. Median of birth intervals was 62 months and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 9 publications
5
8
1
1
Order By: Relevance
“…We found a higher likelihood of SBI among women who gave their most recent birth at the age of 19 or earlier. Our finding of a relatively high prevalence of SBI among younger women is similar to that reported in some studies conducted in LMICs (16,33,38,39). In most LMICs, many women marry before reaching 18.…”
Section: Discussionsupporting
confidence: 90%
“…We found a higher likelihood of SBI among women who gave their most recent birth at the age of 19 or earlier. Our finding of a relatively high prevalence of SBI among younger women is similar to that reported in some studies conducted in LMICs (16,33,38,39). In most LMICs, many women marry before reaching 18.…”
Section: Discussionsupporting
confidence: 90%
“…30.97 months. This result is similar to the study by [14], [15] and equal to the report by [2] which stated that women in higher education levels have a higher risk of giving short birth intervals than lower education levels. Many factors affect this condition, such as age and female fertility.…”
Section: Resultssupporting
confidence: 90%
“…43.09 months. These results are in line with research conducted by [2], [15], [16], [34] with the consideration that the better the economic level of a family, the better access to health and knowledge.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…A group of researchers looked at education, age at the last childbirth, ideal family size, modern versus traditional contraceptive method, survival of preceding birth, and infant mortality records, in relation to birth interval. 5 Another group of researchers found out that constructing healthy rooms in the house could protect children from tuberculosis, even when they were exposed to adult with tuberculosis who live in the same house for a long period, made it no longer a risk factor. 6 Evaluation of breastfeeding counseling implementation in Jambi, Sumatra, found that there was no national guideline on proper breastfeeding counseling in 2014, so the researcher used WHO guidelines.…”
Section: Literature On Evidence-based Research That Includes Both Polmentioning
confidence: 99%